RUSSIA'S EXCLUSION FROM THE REGIONAL HUMAN RIGHTS MECHANISM OR HOW HUMAN RIGHTS ARE ENDANGERED IN A SENSITIVE INTERNATIONAL CONTEXT?! - Corneliu BÎRSAN; Laura-Cristiana SPĂTARU-NEGURĂ (Challenges of the Knowledge Society)
The Russian Federation and the ECtHR have never had a very „friendly” relationship; on the contrary, in some periods the relationship between them has even been tense. By joining the Council of Europe in 1996, the Russian Federation also accepted the compulsory jurisdiction of the ECtHR after ratifying the Convention in 1998. After a tumultuous relationship of more than 20 years characterised by non-compliance and rhetorical attacks, in the context of the „military operation on Ukraine” which began in February 2022, the Russian Federation notified the Secretary General on 15.03.2022 of its withdrawal from the Council of Europe and its intention to denounce the ECtHR. Moreover, as of 16.03.2022, the Russian Federation was excluded from the Council of Europe as a result of its aggression against a member state of the organisation - Ukraine, for which reason the Russian state ceased to be a High Contracting Party to the ECHR as of 16.09.2022. This study will attempt to analyse the legal consequences of this exclusion. After all, who „loses” and who „gains” from this exclusion?